The herriverse: Introducing a new kind of Research Method, one that is Structural or even Meta- insofar as it exists in the Reader’s Navigation of the Curated Space and the Possible Contingent Connections as much as in the Objects being Curated; an Epistemic Construction therefore, that is obliquely but absolutely determined by Ontologically Unpredictable Exchanges. (Journal of the Digital Humanities Association of Southern Africa, 2023)
A brief introduction to a new model for online archiving and journal publishing that rejects a print lineage (book or magazine) for online publication but rather embraces a screen-based genealogy, foregrounding both cinematic and gaming approaches to digital design, user experience and navigation. Visit www.herri.org.za.
Keywords: herri; decoloniality; relationality